A CONTRIBUTION TO THE BIOLOGY OF INDIAN SAND V7HITING-SILLAG0 SIHAMA (FORSKAL) - Radhakrishnan, N (Indian Journal of Fisheries, 2015)
The Indian Sand Whiting, belonging to the family Uaginidae (Order Percomorphoidea), is of some importance to the coastal and estuarine fisheries of India. Very little detailed study of this fish seems to have been made, except for a short account of its food and feeding habits by Chacko (1949), notes on the larval and post-larval stages by Gopinath (1942, 1946), general notes by Devanesan and Chidambaram (1948), and observations on the eggs and larvae by Chacko (1950).